The abandonment of traditional agricultural landscape in Slovakia – Analysis of extent and driving forces. (February 2015) - Lieskovský, Juraj; Bezák, Peter; Špulerová, Jana; Lieskovský, Tibor; Koleda, Peter; Dobrovodská, Marta; Bürgi, Matthias; Gimmi, Urs
Abstract: Traditional agricultural landscapes (TAL) in Slovakia represents a mosaic of unique small-scale arable fields and permanent agricultural cultivations such as grasslands, vineyards and high-trunk orchards, which did not change during the collectivization of agriculture from the 1950s to the 1980s. After the change to a market-oriented economy in 1989, the management of these valuable structures decreased rapidly. The aim of this study is to investigate the distribution of TAL in Slovakia and to analyse the driving forces behind their accelerated abandonment. The study was conducted at two scales, i.e. country-wide and in three case-studies. 3013 TAL polygons encompassing 44, 464 ha were mapped from aerial photos, recording basic characteristics such as land-cover composition or degree of management. A detailed field study concerning the attitude of local people to the management of TAL was conducted in three case study areas. The results from the country-wide mapping shows, that 50% of the TAL area is regularly managed, 34% is partly abandoned, and 16% is abandoned. Abandonment occurs most intensively on steep slopes and on less fertile soils. The distance from settlements is important in the case of TAL with dispersed settlements and TAL with arable land and grasslands. Interviews at the case study level showed that financial profit is the main factor, which would motivate the local people to farm the TAL. Around 30% of respondents showed no interest in management. Local farmers identified the financial instruments in agriculture, in the form of unfavourable subsidies and the financial inaccessibility of modern tools and machinery as the main barriers in ideal management, together with an inadequate market and the weak support of local government. In addition, there are other cultural factors that play a role in their abandonment such as changes in the rural culture, attractivity and diversity of other ways of living, lack of successors, health and age constraints, as well as a number of persisting problems regarding unresolved land ownership in some areas. Highlights: 50% of Slovak traditional agricultural landscapes are partly abandoned or abandoned. Abandonment occurs most intensively on steep slopes and less fertile soils. Financial unprofitability of small-scale farming has triggered abandonment. Around 30% of inhabitants has no interest in TAL management. Cultural drivers like changes in the rural culture, diversity of ways of live played the role as well.